Effect of an Online Educational Intervention on Resilience and Care Burden of the Parents of Children With Cancer - Hajar Behzadi; Leili Borimnejad; Marjan Mardani Hamoleh; Shima Haghani (Iran University of Medical Sciences, 2022)
Background & Aims: Most parents of children with cancer experience a care burden. Increasing their resilience can help reduce their care burden. This study aims to determine the effect of online resilience educational intervention on the resilience and care burden of parents of children with cancer. Materials & Methods: This is a single-group study with a pre-test/post-test design. Fifty parents of children with cancer referred to selected medical centers in Tehran, Iran were selected using a continuous sampling method from July 2020 to February 2021 . The data collection tools were a demographic form, Connor-Davidson resilience scale and Novak and Guest's caregiver burden inventory. Resilience education was presented for 4 weeks online. One month after the intervention, post-test assessments were conducted. Data analysis was done using descriptive and inferential statistics (paired t-test) in SPSS software, version 26 software. Results: The Mean±SD resilience score before the intervention was 50.32±21.84 and increased to 78.24±9.16 after the intervention (P<0.001). The Mean±SD total score of care burden before the intervention was 57.18±18.17 and reduced to 24.02±7.45 after the intervention (P<0.001). Conclusion: The online resilience educational program can increase the resilience and reduce the care burden of the parents of children with cancer. It can be used by nursing managers to increase resilience and reduce the care burden of these parents.